2019
DOI: 10.1007/s13595-019-0847-6
|View full text |Cite
|
Sign up to set email alerts
|

Hardwood injury and mortality associated with two shot hole borers, Euwallacea spp., in the invaded region of southern California, USA, and the native region of Southeast Asia

Abstract: & Key message We assessed the impact of the polyphagous shot hole borer (PSHB), Euwallacea whitfordiodendrus (Schedl), and Kuroshio shot hole borer (KSHB), E. kuroshio Gomez and Hulcr, on hardwood trees in southern California, southwestern China, and northwestern Vietnam. The highest levels of mortality were recorded from 10 of 39 tree species in the survey, and these were primarily native tree species. & Context Two invasive shot hole borers represent relatively recent introductions in southern California, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 46 publications
0
51
0
2
Order By: Relevance
“…Most of these introduced species were native to SE Asia ( Haack and Rabaglia 2013 ). In North America, three SE Asian species Euwallacea fornicatus (Eichhoff, 1868), E. kuroshio (Gomez & Hulcr, 2018), and Xyleborus glabratus Eichhoff, 1877, have caused major economic and ecological damage to trees in urban/suburban and natural areas ( Eskalen et al 2013 ; Boland 2016 ; Carillo et al 2016; Hughes et al 2017 ; Coleman et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these introduced species were native to SE Asia ( Haack and Rabaglia 2013 ). In North America, three SE Asian species Euwallacea fornicatus (Eichhoff, 1868), E. kuroshio (Gomez & Hulcr, 2018), and Xyleborus glabratus Eichhoff, 1877, have caused major economic and ecological damage to trees in urban/suburban and natural areas ( Eskalen et al 2013 ; Boland 2016 ; Carillo et al 2016; Hughes et al 2017 ; Coleman et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been recorded from the following hosts under different names: Callerya (Fabaceae), Persea americana (Lauraceae) ([21,22] as Euwallacea sp. #1 and PSHB, respectively), Robinia (Fabaceae) [23], Sambucus (Adoxaceae), Liquidambar (Altingiaceae), Schinus (Anacardiaceae), Alnus (Betulaceae), Ricinus (Euphorbiaceae), Acacia (Fabaceae), Carya , Quercus (Fagaceae), Juglans (Juglandaceae), Umbellaria (Lauraceae), Magnolia (Magnoliaceae), Ficus , Morus (Moraceae), Eucalyptus (Myrtaceae), Fraxinus (Oleaceae), Platanus (Platanaceae), Prunus (Rosaceae), Populus , Salix (Salicaceae), Acer (Sapindaceae), Ailanthus (Simaroubaceae), and Ulmus (Ulmaceae) ([22,24] as PSHB).…”
Section: Resultsunclassified
“…Host plants. This species is known from Sambucus (Adoxaceae), Liquidambar (Altingiaceae), Schinus , Searsia (Anacardiaceae), Ambrosia , Baccharis (Asteraceae), Alnus (Betulaceae), Ricinus (Euphorbiaceae), Quercus (Fagaceae), Cassia , Persea (Lauraceae), Ficus (Moraceae), Eucalyptus (Myrtaceae), Juglans , Pterocarya (Juglandaceae), Magnolia (Magnoliaceae), Fraxinus (Oleaceae), Platanus (Platanaceae), Populus , Salix (Salicaceae), Nicotiana (Solanaceae), and Tamarix (Tamaricaceae) [24,26,27].…”
Section: Resultsunclassified
“…1-infestation proportion expressed as percentage) agreed by the Panel: graphical representation is shown in Figure A.1.1. The insect E. fornicatus is reported to use A. julibrissin as a host plant (Eskalen et al, 2013) The fungus F. euwallaceae is reported to use A. julibrissin as a host plant (de Beer and Paap, 2019;Coleman et al, 2019), also in Israel (Mendel et al, 2017) Some plant species are reported to be used only as feeding hosts by PSHB where reproductive life stages (e.g. tunneling larvae, male beetles) are not reported (non-reproductive host).…”
Section: A123 Possibility Of Spread Within the Nurserymentioning
confidence: 99%